2012
DOI: 10.5194/aab-55-13-2012
|View full text |Cite
|
Sign up to set email alerts
|

Defining and evaluating heat stress thresholds in different dairy cow production systems

Abstract: The aim of this study was to assess the impact of heat stress in dairy cows on test-day records for production traits and somatic cell score (SCS) in the state of Lower Saxony, Germany. Three different production systems were defined: A production system characterized by intensive crop production (=indoor housing), a pasture based production system, and a maritime region. Heat stress was assessed by two temperature-humidity indices (THI) modelled as random regression coefficients in an analysis of variance: On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
99
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 28 publications
13
99
2
9
Order By: Relevance
“…A decline in milk protein with THI was reported by several other authors (e.g. Bouraoui et al, 2002;Gantner et al, 2011;Bruegemann et al, 2012;Hammami et al, 2013). Our results also agree with those of Lambertz et al (2014), who reported a more marked decline in total protein yield with increasing THI in cows with access to pasture than those without.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A decline in milk protein with THI was reported by several other authors (e.g. Bouraoui et al, 2002;Gantner et al, 2011;Bruegemann et al, 2012;Hammami et al, 2013). Our results also agree with those of Lambertz et al (2014), who reported a more marked decline in total protein yield with increasing THI in cows with access to pasture than those without.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors have reported similar declines in milk yield at low THIs or cold temperatures (Rodriquez et al, 1985;Bruegemann et al, 2012). The rate of decrease in milk yield in our study was greater at higher values of THI than at lower values, consistent with the idea that endotherms are more tolerant of low than high body temperatures (Hansen, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The threshold of THI 5 60 was identified for the various regions characterized as a coastal region, a pasture-based region and a region of intensive crop production. Above this threshold heat stress effects on milk and protein yield were found (Brü gemann et al, 2010;Brü gemann et al, 2012). Whenever environmental stressors in dairy cows are discussed, their remarkable adaptive ability to mobilize mechanisms against environmental stressors has to be considered (Nienaber and Hahn, 2007).…”
Section: Discussionmentioning
confidence: 96%